2018
DOI: 10.1111/jnc.14578
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity and cerebral perfusion of rats with acute liver failure: role of L‐glutamine and asymmetric dimethylarginine in L‐arginine‐induced response

Abstract: Cerebral blood flow (CBF) is impaired in acute liver failure (ALF), however, the complexity of the underlying mechanisms has often led to inconclusive interpretations. Regulation of CBF depends at least partially on variations in the local brain L-arginine concentration and/or its metabolic rate. In ALF, other factors, like an increased concentration of asymmetric dimethylarginine (ADMA), an endogenous nitric oxide synthase inhibitor and elevated level of L-glutamine, may contribute to CBF alteration. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(158 reference statements)
1
2
0
Order By: Relevance
“…eNOS is critically involved in the maintenance of adequate cerebral blood flow (CBF) [76]. Therefore, deactivation of eNOS is a likely cause of the CBF impairment in the prefrontal cortex of TAA rats which was consistently observed in the present and in a previous study [77], as well as in studies in which different CBF recording procedures have been used [78]. Importantly in this context, several reports have implicated the participation of nNOS in CBF control (Santizo et al, 2000, Chi et al, 2003.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…eNOS is critically involved in the maintenance of adequate cerebral blood flow (CBF) [76]. Therefore, deactivation of eNOS is a likely cause of the CBF impairment in the prefrontal cortex of TAA rats which was consistently observed in the present and in a previous study [77], as well as in studies in which different CBF recording procedures have been used [78]. Importantly in this context, several reports have implicated the participation of nNOS in CBF control (Santizo et al, 2000, Chi et al, 2003.…”
Section: Discussionsupporting
confidence: 87%
“…Isolated prefrontal cortex tissue was homogenized (1/5; w/v) in Locke buffer (154 mM NaCl, 5.6 mM KCl, 1.0 mM MgCl2, 2.3 mM CaCl2, 8.6 mM HEPES, 5.6 mM glucose, 0.1 mM glycine, pH 7.4) and diluted 10 times. Homogenate samples were incubated with NOS substrate L-arginine (100 µM) and/or L-NAME (100 µM), EDTA (1 mM), BH4 (100 nM) for 10 min, at 22-25 • C. The dose of L-arginine was chosen based on the literature and our previous study [77]. Subsequently, 10 µM carboxy-H2 DCFDA was added to each reaction mixture.…”
Section: Reactive Oxygen Species Measurementmentioning
confidence: 99%
“…The importance of this mechanism comes to light when confronted with the previous observation that l -glutamine infusion in the absence of hyperammonemia impairs cerebrovascular CO 2 reactivity, most likely by reducing l -arginine availability and NO synthesis [ 90 ]. A recent study from our laboratory demonstrated strong differences in the reactivity of the middle cerebral arteries and in their response to extravascular l -arginine application between vessels isolated from rats with TAA-induced HE and control animals, implicating that impaired vascular tone of cerebral arteries, which may involve, among other factors, their persistent exposure to high l -glutamine [ 91 ].…”
Section: Mitochondrial-derived Reactive Oxygen Species (Ros) In the E...mentioning
confidence: 99%